1979
DOI: 10.1073/pnas.76.10.5274
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of autoimmune disease in (NZB/NZW)F1 female mice by using fractionated total lymphoid irradiation.

Abstract: Adult female (NZB/NZW)F1 hybrid mice with documented autoimmune glomerulonephritis resembling systemic lupus erythematosus were treated with fractionated total

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Because cells from the irradiated rats in experiment 1 had failed to respond to PHA 43 days earlier, these data indicate that recovery of at least some cellular functions had occurred by 7 weeks after completion of TLI. Our findings in rats are consistent with previous demonstrations in mice that TLI can suppress B cell responses to primary immunization (7) or abnormal antibody titers present in the syndromes that resemble systemic lupus erythematosus in the NZB/NZW (8,9) and MRL/l (10) strains, and can impair T cell functions in mice (1-6,10,12) and rats (11,12). In addition, the transient nature of the T cell suppression produced by TLI is similar to the observation of Slavin et a1 (1,2) that murine lymphocytes had regained the capacity to react to alloantigens in mixed lymphocyte cultures by 70 days after TLI.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Because cells from the irradiated rats in experiment 1 had failed to respond to PHA 43 days earlier, these data indicate that recovery of at least some cellular functions had occurred by 7 weeks after completion of TLI. Our findings in rats are consistent with previous demonstrations in mice that TLI can suppress B cell responses to primary immunization (7) or abnormal antibody titers present in the syndromes that resemble systemic lupus erythematosus in the NZB/NZW (8,9) and MRL/l (10) strains, and can impair T cell functions in mice (1-6,10,12) and rats (11,12). In addition, the transient nature of the T cell suppression produced by TLI is similar to the observation of Slavin et a1 (1,2) that murine lymphocytes had regained the capacity to react to alloantigens in mixed lymphocyte cultures by 70 days after TLI.…”
Section: Discussionsupporting
confidence: 92%
“…TLI initiated at the onset of collagen arthritis decreased humoral and cellular responses to collagen but did not affect the severity of arthritis. These data demonstrate that both TLI and cyclophospharnide are immunosuppressive in an experimentally inducible autoimmune disease.The immunosuppression produced in mice by fractionated total lymphoid irradiation (TLI) can pro-long allogeneic skin (1,2) and bone marrow (2-5) engraftment , expedite the development of tolerance to foreign protein antigens (6), decrease the antibody response to a foreign antigen (7), and ameliorate autoimmune disease in the NZB/NZW (8,9) and MRL/1 (10) strains. In rats, TLI has been shown to facilitate the induction of allograft tolerance (1 1,12), to decrease, preferentially, lymphocyte concentrations in the blood, and to partially suppress adjuvant arthritis (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer of a mixture of stem cells obtained from MRL/lpr and MRL/ +/+ results in a disease similar to that observed in the MRL/ Ipr donor mice. This again suggests that the disease is mainly caused by a basic and dominant defect of the MRL/lpr haematopoietic stem cells, rather than by the absence of active down-regulation of anti-self reacting lymphocytes [7,23,26]. Conversely, if one eliminates MRL/lpr stem cells in the original hosts by allogeneic BMT, utilizing stem cells from normal strains, the resulting chimaeras no longer exhibit SLElike manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Development of SLElike autoimmune syndrome is T cell-dependent, as documented by experiments involving neonatal thymectomy [24] as well as by in vivo treatment with anti-Thy 1.2 antibodies [25]. Previous studies on mice treated with ionizing irradiation, involving either TBI (12], or TLI [26,27]. showed that irradiation markedly suppresses T cell-dependent immune function by inducing selective T cell lymphopenia [28].…”
Section: Effect Of Sbmt On Histological Manifestations Of Renal Diseasementioning
confidence: 99%